Metabolisme Benzonitril oleh Flavobacterium sp. NUB 1 - Sulistinah, Nunik; Sunarko, Bambang; Thontowi, Ahmad (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTMetabolism of Benzonitriles by Flavobacterium sp. NUB 1. Flavobacterium sp. NUB 1 was isolated from industrial waste of PT. Petrokimia Gresik. The bacterium was able to utilize benzonitrile and acetonitrile and propionitril as the sole source of carbon and nitrogen. Growth on benzonitrile gave higher growth rate and biomass yield than growth on acetonitrile and propionitrile. When Flavovobacterium sp. NUB1 grew on benzonitril 15 mM , the doubling time is 9 hours 54 minutes and the specific growth rate (?) was 0,07 h-1. Whole cell of Flavobacterium sp. NUB 1 could hydrolyzed aromatic and aliphatic nitriles. The bacteria isolate has ability in metabolism of acetonitrile greater than benzonitrile. Activity of nitrile hydratase and amidase are more dominant than nitrilase in metabolism of benzonitrile.Key words: Biodegradation, benzonitril, Flavobacterium sp. NUB 1, nitrile-hydratase,amidase, nitrilase